Impact of pneumoperitoneum pressure on cardiac output in laparoscopic surgery - Fuwei Qi; Bing Wang; Fan Fei; Qiang Guo; Zhong Zheng; Guangyu Yang; Ke Li (BMC Anesthesiology)
Abstract Objective To assess the impact of pneumoperitoneum pressure on cardiac output (CO) in patients undergoing laparoscopic surgery using transesophageal echocardiography. Methods Fifty patients (26 men, 24 women; age, 55–85 years old) who scheduled for laparoscopic colorectal cancer resection under general anesthesia at the First People's Hospital of Taicang (March 2021–December 2022) were enrolled. Patients were randomly assigned to three groups based on pneumoperitoneum pressure: group A (10 mmHg), group B (12 mmHg), and group C (14 mmHg). Left ventricular outflow tract diameter (LVOT) and velocity time integral (VTI) were measured using transesophageal echocardiography to calculate CO). Results Baseline characteristics and intraoperative data were comparable among groups (P > 0.05). Post-anesthesia, heart rate, mean arterial pressure (MAP), systolic blood pressure (SBP), and diastolic blood pressure (DBP) showed no significant differences among groups (P > 0.05). However, CO in all groups was lower than normal reference values after anesthesia induction (P < 0.05) and further declined following pneumoperitoneum establishment (P < 0.05). Group C exhibited significantly lower CO than Groups A and B five minutes after pneumoperitoneum initiation (P < 0.05). Conclusion Pneumoperitoneum pressure significantly impacts CO during laparoscopic surgery. Transesophageal echocardiography provides an effective method for monitoring hemodynamic changes and optimizing perioperative management.